Mutations in SETBP1 are recurrent in myelodysplastic syndromes and often coexist with cytogenetic markers associated with disease progression. (24th July 2013) - Fernandez‐Mercado, Marta; Pellagatti, Andrea; Di Genua, Cristina; Larrayoz, Maria Jose; Winkelmann, Nils; Aranaz, Paula; Burns, Adam; Schuh, Anna; Calasanz, Maria Jose; Cross, Nicholas C. P.; Boultwood, Jacqueline
Summary Whole exome sequencing was performed in a patient with myelodysplastic syndrome before and after progression to acute myeloid leukaemia. Mutations in several genes, including SETBP1, were identified following leukaemic transformation. Screening of 328 patients with myeloid disorders revealed SETBP1 mutations in 14 patients (4·3%), 7 of whom had −7/del(7q) and 3 had i(17)(q10), cytogenetic markers associated with shortened overall survival and increased risk of leukaemic evolution. SETBP1 mutations were frequently acquired at the time of leukaemic evolution, coinciding with increase of leukaemic blasts. These data suggest that SETBP1 mutations may play a role in MDS and chronic myelomonocytic leukaemia disease progression.